2012
DOI: 10.1377/hlthaff.2012.0364
|View full text |Cite
|
Sign up to set email alerts
|

Early Results Show WellPoint’s Patient-Centered Medical Home Pilots Have Met Some Goals For Costs, Utilization, And Quality

Abstract: Primary care must be reengineered to improve outcomes and affordability. To achieve those goals, WellPoint invested in ten patientcentered medical home pilots that encourage care coordination, preventive care, and shared decision making. Two of the three pilots described in this article-in Colorado and New Hampshire-layer incentive payments for care coordination and quality improvement on top of a traditional fee-for-service payment. The third-in New York-pays doctors an enhanced fee that is tied to achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…20 WellPoint uses "value-based payments" to supplement FFS reimbursements for primary care providers in PCMHs. 21 In this way, payments reward quality and efficiency and are intended to compensate physicians for non-visit-based services, such as maintaining disease registries. Several multipayer PCMH pilots provide a "management fee" (based on panel size) to participating providers.…”
Section: Value-based Supplemental Paymentsmentioning
confidence: 99%
“…20 WellPoint uses "value-based payments" to supplement FFS reimbursements for primary care providers in PCMHs. 21 In this way, payments reward quality and efficiency and are intended to compensate physicians for non-visit-based services, such as maintaining disease registries. Several multipayer PCMH pilots provide a "management fee" (based on panel size) to participating providers.…”
Section: Value-based Supplemental Paymentsmentioning
confidence: 99%
“…3 Research evaluating the PCMH's effectiveness in achieving the goals of improved care quality, patient experience, and reduced healthcare costs has encouraged further refinement of the model. [4][5][6][7][8][9][10][11] Facilitators and barriers to the creation of a successful PCMH have been explored in a limited number of heterogeneous settings, including small practices, large group practices, high-performing practices, and safety net clinics. [12][13][14][15][16][17] To date, significant challenges have been identified; specifically, the investment of resources for infrastructure changes and the leadership skills needed to guide an organization through paradigm-shifting cultural change.…”
Section: Introductionmentioning
confidence: 99%
“…7 One insurer recently reported a significant positive return on investment. 8 A review in 2010 concluded that "investing in primary care patient centered medical homes results in improved quality of care and patient experiences, and reductions in expensive hospital and emergency department utilization." 9 In one study, levels of clinicians' emotional exhaustion in a PCMH practice was significantly reduced compared to levels at two control clinics (14 % vs. 35 %, p<0.001).…”
Section: Ethics and Implementationmentioning
confidence: 99%